2012
DOI: 10.1021/jz300967q
|View full text |Cite
|
Sign up to set email alerts
|

Single-Molecule Surface-Enhanced Raman Scattering: Can STEM/EELS Image Electromagnetic Hot Spots?

Abstract: Since the observation of single-molecule surface-enhanced Raman scattering (SMSERS) in 1997, questions regarding the nature of the electromagnetic hot spots responsible for such observations still persist. For the first time, we employ electron-energy-loss spectroscopy (EELS) in a scanning transmission electron microscope (STEM) to obtain maps of the localized surface plasmon modes of SMSERS-active nanostructures, which are resolved in both space and energy. Single-molecule character is confirmed by the bianal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
81
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(84 citation statements)
references
References 52 publications
3
81
0
Order By: Relevance
“…It is important to note that since CL measures only the vertical field component, field enhancements in interparticle "hot spots" appear in CL as dark gaps bounded by bright particle edges. 57 At short wavelengths, a strong spatial asymmetry in the CL map is observed: the smaller satellite particles appear as asymmetric dipoles ( Figure 6C,D), while the bright "hot spot" adjacent to the central particle is observed to be wavelength-dependent. For the leftmost satellite particle, this hot spot is strongest near the UV edge of our CL detection range, while the rightmost particle exhibits a maximum at 430 nm because it has both a larger diameter and a larger gap.…”
Section: Articlementioning
confidence: 92%
“…It is important to note that since CL measures only the vertical field component, field enhancements in interparticle "hot spots" appear in CL as dark gaps bounded by bright particle edges. 57 At short wavelengths, a strong spatial asymmetry in the CL map is observed: the smaller satellite particles appear as asymmetric dipoles ( Figure 6C,D), while the bright "hot spot" adjacent to the central particle is observed to be wavelength-dependent. For the leftmost satellite particle, this hot spot is strongest near the UV edge of our CL detection range, while the rightmost particle exhibits a maximum at 430 nm because it has both a larger diameter and a larger gap.…”
Section: Articlementioning
confidence: 92%
“…As reported by Stranahan et al by using super-resolution imaging as a powerful new tool the centroid position of the SERS field could be mapped to within 10 nm resolution, revealing a spatial relationship between the SM-SERS centroid position and the highest SERS intensity [80]. Meanwhile, by employing electron-energy-loss spectroscopy (EELS) in a scanning transmission electron microscope (STEM), Mirsaleh-Kohan et al [81] obtained maps of the localized surface plasmon models of SM-SERS-active nanostructures, in which the SM characteristics were confirmed by the bianalyte approach. Another more promising and most widely used system for SM and single-particle SERS is the combination of Raman microscopy with atomic force microscopy (AFM) as indicated in figure 4c, where, an AFM-coupled nano-Raman spectroscopy setup is described for nanoscale detection [69].…”
Section: Devices/systems For Single-molecule Surfaceenhanced Raman Spmentioning
confidence: 99%
“…These photoexcited electrons directly get injected into the nearby TiO 2 CB due to the formation of Schottky barrier at the metal semiconductor interface. It was also suggested that the hot spots (plasmon decay producing intensely hot electrons) appear on the sharp edges and corners of TiO 2 where the electric field intensity of SPR is several times higher than that of the incident electric field of the photon [201][202][203][204]. Electron hole pairs are generated by surface plasmon decay and the rate of generation is intensified by the local filed enhancement on the hot spot regions (Fig.…”
Section: Photocatalytic Activity Of Palladium Deposited Titania (Pd/tmentioning
confidence: 99%